RELEVANCE OF THE LAW ON THE ELECTION OF REGIONAL HEADS WITH LAW ABOUT LOCAL GOVERNMENT - Erlina (Faculty of Law-Universitas Bandar Lampung, 2022)
The role of political parties as bearers of the functions of socialization, education, participation, and political recruitment is a very effective medium in triggering the political participation of local people. The existence of a discourse on changing the Regional Head Election system in the Regional Head Election Bill must be formulated in a comprehensive manner. So that the result will make the quality of democracy in Indonesia better, and whether direct elections for governors, regents or mayors will have changes and variations for the better in the future. The main problems in this research are: How is the relevance or suitability of the Draft Law on Regional Head Elections to Law concerning Regional Government. The results of this study conclude that: There is relevance between the Bill on the General Election of Regional Heads and Law concerning Regional Government, namely regarding the principle that regional head elections are carried out democratically based on the principles of direct, general, free, confidential, honest and fair. Suggestions that can be submitted are to the government, to obtain a regional head election system that reflects responsive democratic values, it should be studied in depth in the discussion of the Regional Head Election Bill. To the DPR, it is necessary to more deeply examine the various potentials and practices of informality that may arise accompanying the post-conflict local election.